Cellular Changes in Lungs of Mice Infected with Influenza Virus: Characterization of the Cytotoxic Responses - Wyde, Philip R. (1978)
Transpleural lavage of lungs from uninfected C3H mice yielded an average of 300,000 leukocytes per mouse. This number increased eightfold within 6 days after intranasal inoculation with virulent influenza A/Hong Kong/68 (H3N2) virus. Macrophages and lymphocytes in approximately equal numbers comprised 90% or more of the leukocytes both before and during infection. B, T, and null lymphocytes comprised, respectively, 9, 21, and 18% of the leukocytes before infection and 7, 26, and 5% by day 6. In absolute numbers, macrophages and T lymphocytes provided the major increments during infection. Cytotoxic activity of mononuclear cells from lung lavages was compared in a chromium release assay using syngeneic L929 target cells with the activity of mediastinal lymph nodes, spleens, and peripheral blood of uninfected and infected C3H mice. Nonspecific cytotoxicity for target cells infected with H3hkNeq1 or B/Lee influenza virus was found with mononuclear cells from uninfected mice. This activity tended to be highest with lavage leukocytes and was associated with adherent cells, presumably macrophages. Increased virus-specific cytotoxicity was detected with lavage cells by day 6 and persisted through day 9, the period of maximal pneumonia. Similar cytotoxic activity also appeared in cells from the nodes and spleen at this same time but was not detected in peripheral blood cells. The virus-specific cytotoxicity of lavage cells was due largely to a nonadherent cell possessing Fc receptors and theta antigen but lacking C3 receptors; these properties are compatible with actively cytotoxic T lymphocytes. The cytological characteristics of the infiltrating leukocytes and the cytotoxicity data suggest that the local T cell response to influenza virus infection in the lung is a major contributor to the pneumonia observed in this mouse model.